Near-infrared pH-sensitive probes based on aza-Nile Blue for detecting interactions between mitochondria and lysosomes - Wang, Hui; Xu, Xu; Ni, Wen-Pei; Sun, Ru; Zhang, Yi; Ge, Jian-Feng (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2025)
Near-infrared pH-sensitive probes based on aza-Nile Blue for detecting interactions between mitochondria and lysosomes. [Display omitted] •Water soluble and high molar extinction coefficient.•Linear response ranges of 4 pH units around 8.0.•Visualization of mitochondrial and lysosomal dynamic interactions. The pKa values of mitochondrial fluorescent probes based on pH response differ significantly from the pH of the mitochondrial matrix, making the development of mitochondria-targeted pH probes with appropriate pKa values essential for accurately monitoring mitochondrial pH fluctuations. In this paper, three mitochondria-targeted near-infrared fluorescent probes 5a–5c were successfully developed by introducing nitrogen atom at the 4-position of Nile Blue and modulating the pKa through the formation of intramolecular hydrogen bonding. Probes 5a–5c exhibited ultra-high molar extinction coefficients up to 105 M−1 cm−1, along with excellent photostability and sensitive pH response properties. The fluorescence intensities of 5a–5c enhanced 12–14-fold, while the fluorescence quantum yields increased from 1.2 %−2.5 % to 13 %−16 % with the pH decreasing from 10 to 4.0 (including only 0.5 % cosolvent). In addition, linear relationships between pH and maximum fluorescence intensity were established with high correlation coefficient (R2 = 0.99) from pH 5.2 to 9.2. Based on the low toxicity and mitochondrial targeting ability, probes 5a–5c migrated from mitochondria to lysosomes during starvation and rapamycin-induced autophagy, allowing real-time tracking of mitochondrial pH variations using fluorescence intensity and colocalization coefficient as parameters. Notably, dynamic changes between mitochondria and lysosomes were observed in real time in the mitochondrial damage model constructed by hydrogen peroxide. In conclusion, probes 5a–5c have excellent optical properties and biocompatibility, underscoring their significance in monitoring mitochondrial physiological and pathological processes.